Epigenetic regulation of the nuclear genome associated with mitochondrial dysfunction in Leber’s hereditary optic neuropathy (LHON) - Aswathy P. Nair; Ambika Selvakumar; Janani Gopalarethinam; B. Abishek Kumar; Balachandar Vellingiri; Mohana Devi Subramaniam (Human Genome Variation)
Abstract Leber’s hereditary optic neuropathy (LHON) is a mitochondrial hereditary disease in which visual loss affects complex 1 activity of the electron transport chain of mitochondria. It first manifests as painless dulling or blurry in one or even both eyes, and as it develops, sharpness and color perception are lost. In addition to primary mitochondrial DNA (mtDNA) mutations, there are also other environmental and epigenetic factors involved in the pathogenesis of LHON. One of the most common locations for deadly pathogenic mutations in humans is the human complex I accessory NDUFS4 subunit gene. The iron-sulfur clusters of the electron input domain were distorted in the absence of NDUFS4, which reduced complex I function and elevated the production of reactive oxygen species. Therefore, here, we studied the epigenetic alterations of NDUFS4 by focusing on histone activation and repressive markers. We isolated peripheral blood mononuclear cells (PBMCs) from LHON patients and healthy individuals and examined epigenetic modifications in ND4 mutant cells and control cells. Chromatin immunoprecipitation-qRT PCR (ChIP-qRT PCR) assays were performed to investigate the modifications of histones. In comparison to their controls, both LHON patients and ND4 mutant cells exhibited a significant enrichment in activation and repressive markers. This finding indicates that these modifications might mitigate the impact of LHON mutations on complex 1 and aid in elucidating the mechanism underlying the progression of LHON disease.